Point‐of‐care hip ultrasound leads to expedited results in emergency department patients with suspected septic arthritis - Christopher Thom; Azhar Ahmed; Matthew Kongkatong; James Moak (Journal of the American College of Emergency Physicians Open)
Abstract Background The evaluation of septic hip arthritis often incorporates the utilization of hip ultrasonography to determine the presence of a hip joint effusion, as well as to guide arthrocentesis. Point‐of‐care (POC) hip ultrasound has previously been demonstrated to be accurate when performed by the emergency physician. Time to diagnosis and subsequent intervention in septic arthritis (SA) is critical to favorable outcomes. Methods Retrospective single‐center study of all emergency department (ED) patients who had a POC or radiology hip ultrasound or arthrocentesis as part of their ED evaluation for SA in a 3‐year period. We investigated the difference in time to obtain hip ultrasonography results and the time to arthrocentesis between radiology and emergency physician‐performed studies in cases of suspected septic hip arthritis. Results Seventy‐four patients met inclusion criteria. The median time to hip ultrasound completion was 68 (interquartile range [IQR], 38.8–132) minutes in the emergency physician‐performed ultrasound group versus 208.5 (IQR, 163.8–301.3) minutes for the radiology group (P < 0.001). A total of 17 patients had a hip arthrocentesis performed. Time to arthrocentesis was 211 (IQR 141.3–321.5) minutes in the emergency physician‐performed arthrocentesis group and 602 (IQR 500–692) minutes in the radiology arthrocentesis (P < 0.001). Conclusion There was a statistically shorter time to ultrasound result and arthrocentesis when POC hip ultrasound was utilized by the emergency physician. Given that unfavorable outcomes in SA are associated with delay in treatment, further study is warranted to determine if emergency physician‐performed hip ultrasound and arthrocentesis could lead to improved patient‐centered clinical end points.